Patterns of Economic Allocation and Decision Making of Mountain Farming Women in Rural Development - Ismail, Ashari (Jurnal Office, 2023)
Development is planned change, has goals with sustainable programs, and is related to the time dimension. The aim of this research is to reveal the economic allocation patterns and power of mountain farming women as main and additional breadwinners in rural development. The approach used in this research is a naturalistic qualitative approach with proportional sampling. Data collection using in-depth interviews and observations. The research results show that the economic allocation pattern of female mountain farmers is a work pattern for mountain farmers who are productive not only as additional providers, but also as main breadwinners and have an important contribution to rural development. This pattern of economic allocation for women farmers continues to rely on rural cultural values and the awareness of women farmers to contribute economically to their families and the wider community for rural development. The pattern of power allocation of mountain farming women in the domestic realm and wider society, with the real economic contributions they have made, has an effect on the tendency to be perceived as equal to men, in every development role.